PENGARUH KUALITAS PROGRAM PELATIHAN DAN KOMPETENSI INSTRUKTUR TERHADAP PENINGKATAN KOMPETENSI PESERTA DIDIK MELALUI MOTIVASI BELAJAR - Fatmawati; Fathorrahman; Widi Dewi S (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Improving student competence is an important aspect of training institution success, especially in institutions oriented toward work-skill development. LPK Cendana Training Center Samarinda, as a training institution, plays a role in providing quality training programs, supported by instructor competence and students' learning motivation. This study aims to analyze the influence of Training Program Quality and Instructor Competence on Student Competency Improvement, with Learning Motivation as an intervening variable. A quantitative approach was used, with data analyzed using Smart PLS. The results of the study show that the quality of training programs and instructor competencies have a positive and significant effect on learning motivation and improvement of student competence. Learning motivation also has a positive effect on improving student competence and has been proven to mediate the influence of the quality of training programs and instructor competencies on improving student competence. All the relationships tested showed a p < value of 0.05. These findings show that student competence improvement is not only directly influenced by the quality of training programs and instructor competence, but also strengthened by students' learning motivation. This research contributes to training institutions by helping them design more effective programs through improving training quality, strengthening instructor competence, and creating a learning environment that encourages student motivation.